KAJIAN POTENSI KENDARAAN BERMOTOR MENJADI BARANG KENA CUKAI - Budhi Setyawan; Gea Meryna Sabrie (JURNAL PERSPEKTIF BEA DAN CUKAI, 2022)
Based on research by the Global Alliance on Health and Pollution (GAHP), the fourth largest contributor to deaths from pollution is Indonesia. The number of deaths from air pollution is not far related to the number of motorized vehicles in Indonesia, because the more motorized vehicles, the more carbon emissions are released thereby increasing air pollution in Indonesia. In-Law number 11 of 1995 concerning Excise jo. Law Number 39 of 2007, Excisable Goods stated in article 2 paragraph (1) as certain items that have characteristics of use can have a negative impact on the community or the environment. In article 4 paragraph (2), the addition or reduction of types of excisable goods is regulated further by a Government Regulation. Motorized vehicles fall into the two criteria above. This study aims to assess the potential feasibility of imposing excise duties on motorized vehicles. The research methodology was carried out using literature studies and data analysis related to excise revenue and the number of motorized vehicles in Indonesia. The results of this study recommend that motorized vehicles are eligible to become Excisable Goods. Excise tax rates can be ad valorem tariffs, following the best practices of countries that have imposed an excise tax on motorized vehicles. Keywords: extensification, excise, excisable goods, motorized vehicles, the Directorate General of Customs and Excise.